Strategic Planning in Practice: The Case of Utah’s Statewide Strategic Plan on Homelessness - Lina Svedin; Jesus N. Valero (Journal of Participatory Research Methods)
Much has been written theoretically about the concept and process of strategic planning. However, less is written in the scholarship about the nuts and bolts of strategic planning such as experiences in the practice of community engaged research to develop plans that achieve strategic change. In this study, we reflect on a recent partnership with a public agency to draft a statewide strategic plan on homelessness and we outline in detail the process that we undertook to build the partnership and engage in community-focused and driven research. After engaging in a reflective exercise, we construct a three-phase process of strategic planning that was informed by both the existing literature and the nature of the community engaged partnership with the public agency.